Carbon aerogel adsorbent material and method of making same
Patent Information
- Application Number
- CN202311795145.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-25
AI Technical Summary
[0003]但是,相关技术提供的吸附材料,例如:活性炭,其虽然具有较大的比表面积,但是对于甲醛的吸附仍然具有局限性,在吸附时,不具备对于甲醛的高选择性,会同时吸附其他气体,导致吸附性能快速下降,且不具备高温稳定性,容易在高温时脱吸附,导致二次污染
[0023]本发明的碳气凝胶吸附材料的制备方法,先制得孔结构可调的中孔金属离子掺杂的碳气凝胶前体,其由球状纳米粒子相互连结而成,具有较高的比表面积和发达的孔结构,能为甲醛气体分子传输提供充足的通道,之后在金属离子掺杂的碳气凝胶前体的负载的有机胺,能利用有机胺与甲醛充分发生化学反应,以实现对于甲醛的高选择性去除效果,并且通过有机胺与甲醛发生化学反应去除甲醛,还能避免在高温下释放甲醛造成二次污染的问题,即保证了高温下去除甲醛的稳定性。
Smart Images

Figure BDA0004627496220000101 
Figure BDA0004627496220000111 
Figure BDA0004627496220000112
Abstract
Description
Technical Field
[0001] This invention relates to the field of purification and adsorption materials technology, and more specifically, to carbon aerogel adsorption materials and their preparation methods. Background Technology
[0002] Formaldehyde is a common pollutant from home renovations, and adsorption is a common method for removing it. Commonly used adsorption materials include activated carbon, silica gel, zeolite, and activated alumina.
[0003] However, the adsorption materials provided by related technologies, such as activated carbon, although they have a large specific surface area, still have limitations in adsorbing formaldehyde. During adsorption, they do not have high selectivity for formaldehyde and will adsorb other gases at the same time, resulting in a rapid decline in adsorption performance. Furthermore, they do not have high temperature stability and are prone to desorption at high temperatures, leading to secondary pollution. Summary of the Invention
[0004] The purpose of this invention is to provide a carbon aerogel adsorbent material and its preparation method. The carbon aerogel adsorbent material prepared by this method has high selectivity for formaldehyde, can effectively remove formaldehyde, and has high temperature stability, so it is not easy to desorb at high temperature and cause secondary pollution.
[0005] This invention is implemented as follows:
[0006] In a first aspect, the present invention provides a method for preparing a carbon aerogel adsorbent material, comprising:
[0007] A pre-mixed solution was prepared by combining metal salts, phenolic monomers, aldehyde monomers, and hexadecyltrimethylammonium bromide.
[0008] A sol-gel reaction was carried out in a pre-mixed solution under preset temperature conditions to obtain a metal ion-doped carbon aerogel precursor.
[0009] The metal ion-doped carbon aerogel precursor was dried to obtain a dry gel.
[0010] Carbon aerogel is obtained by carbonizing the dry gel, washing it with water, and drying it.
[0011] Organic amines were loaded onto carbon aerogels.
[0012] In an optional implementation, the metal salt includes a nickel salt or a copper salt.
[0013] In an optional embodiment, the nickel salt includes at least one of nickel nitrate, nickel chloride, and nickel bromide; the copper salt includes copper nitrate.
[0014] In an optional embodiment, the phenolic monomer includes at least one of resorcinol and 3-aminophenol.
[0015] In an optional embodiment, the aldehyde monomer includes at least one of formaldehyde, furfural, and 5-(hydroxymethyl)furfural.
[0016] In an optional embodiment, the organic amine in the organic amine solution includes at least one of polyethyleneimine, triethylenetetramine, amino acids, and imidazolidinone.
[0017] In an optional implementation, the preset temperature is 50-90°C; the sol-gel reaction time is 4-6 days.
[0018] In an optional embodiment, the method for preparing the carbon aerogel adsorbent material further includes: loading an organic amine onto the carbon aerogel and then spraying it onto a porous substrate.
[0019] In an optional embodiment, the porous substrate includes at least one of paper honeycomb, porous ceramics, porous glass, and porous carbon materials.
[0020] In an optional embodiment, the carbonization step is carried out under a nitrogen atmosphere, and the temperature of the carbonization step is 800-1000°C, with a heating rate of 4-6°C / min.
[0021] Secondly, the present invention provides a carbon aerogel adsorbent material, which is prepared by the carbon aerogel adsorbent preparation method of any of the foregoing embodiments.
[0022] The present invention has the following beneficial effects:
[0023] The method for preparing the carbon aerogel adsorbent material of the present invention first prepares a mesoporous metal ion-doped carbon aerogel precursor with tunable pore structure, which is composed of interconnected spherical nanoparticles, has a high specific surface area and a well-developed pore structure, and can provide sufficient channels for the transport of formaldehyde gas molecules. Then, an organic amine loaded on the metal ion-doped carbon aerogel precursor can fully react with formaldehyde to achieve a highly selective removal effect of formaldehyde. Furthermore, the removal of formaldehyde through the chemical reaction between organic amine and formaldehyde can avoid the problem of secondary pollution caused by the release of formaldehyde at high temperatures, thus ensuring the stability of formaldehyde removal at high temperatures. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0025] This invention provides a method for preparing a carbon aerogel adsorbent material, comprising: preparing a pre-mixed solution of a metal salt, a phenolic monomer, an aldehyde monomer, and hexadecyltrimethylammonium bromide; subjecting the pre-mixed solution to a sol-gel reaction under a preset temperature condition to obtain a metal ion-doped carbon aerogel precursor; drying the metal ion-doped carbon aerogel precursor to obtain a dry gel; carbonizing the dry gel, followed by washing and drying with water to obtain a carbon aerogel; and loading an organic amine onto the carbon aerogel.
[0026] The method for preparing the carbon aerogel adsorbent material of the present invention first prepares a mesoporous metal ion-doped carbon aerogel precursor with tunable pore structure, which is composed of interconnected spherical nanoparticles, has a high specific surface area and a well-developed pore structure, and can provide sufficient channels for the transport of formaldehyde gas molecules. Then, an organic amine loaded on the metal ion-doped carbon aerogel precursor can fully react with formaldehyde to achieve a highly selective removal effect of formaldehyde. Furthermore, the removal of formaldehyde through the chemical reaction between organic amine and formaldehyde can avoid the problem of secondary pollution caused by the release of formaldehyde at high temperatures, thus ensuring the stability of formaldehyde removal at high temperatures.
[0027] Optionally, the step of preparing a pre-mixed solution from metal salt, phenolic monomer, aldehyde monomer and hexadecyltrimethylammonium bromide specifically includes: dissolving phenolic monomer, hexadecyltrimethylammonium bromide and metal salt in water, and then adding aldehyde monomer solution to mix, thereby obtaining a pre-mixed solution.
[0028] Furthermore, the mass ratio of the phenolic monomer to hexadecyltrimethylammonium bromide is 100:1 to 2, for example: 100:1, 100:1.2, 100:1.5, 100:1.65, 100:1.8, 100:2, etc.; the mass ratio of the phenolic monomer to the volume ratio of water is 10:13 to 16, in g:mL, for example: 10:13, 10:14, 10:14.6, 10:15, 10:16, etc.; the mass ratio of the metal salt to the volume ratio of water is... The ratio is 1:8 to 12, in g:mL, for example: 1:8, 1:9, 1:10, 1:11, 1:12, etc.; the mass concentration of the aldehyde monomer solution is 30-40%, for example: 30%, 33%, 35%, 37%, 40%, etc.; and the mass ratio of phenolic monomer to volume of aldehyde monomer solution is 10:11 to 14, in g:mL, for example: 10:11, 10:12, 10:12.6, 10:13, 10:14, etc.
[0029] Alternatively, the carbon aerogel can be mixed with an organic amine solution to load the organic amine onto the carbon aerogel.
[0030] Optionally, the mass ratio of organic amine in the organic amine solution to carbon aerogel is 3-5:12-18, for example: 5:15, 3:12, 3:13, 4:15, 4:16, 4:17, 5:12, 5:18, etc.
[0031] Alternatively, the metal salt may include nickel or copper salts.
[0032] Furthermore, nickel salts include at least one of nickel nitrate, nickel chloride, and nickel bromide; copper salts include copper nitrate.
[0033] Optionally, the phenolic monomer includes at least one of resorcinol and 3-aminophenol.
[0034] Alternatively, the aldehyde monomers include at least one of formaldehyde, furfural, and 5-(hydroxymethyl)furfural.
[0035] Optionally, the organic amine in the organic amine solution includes at least one of polyethyleneimine, triethylenetetramine, amino acids, and imidazolidinones, wherein the amino acid may refer to L-cysteine.
[0036] Optionally, the preset temperature is 50-90℃, such as 50℃, 60℃, 70℃, 80℃, 90℃, etc., without specific limitation; the sol-gel reaction time is 4-6 days, such as 4 days, 5 days, 6 days, etc., and can also refer to 48-72h, such as 48h, 52h, 58h, 60h, 63h, 65h, 68h, 70h, 72h, etc., without specific limitation.
[0037] Optionally, the drying temperature of the metal ion-doped carbon aerogel precursor can be 80-120℃, such as 80℃, 90℃, 100℃, 110℃, 120℃, etc.; the drying time can be 10-15h, such as 10h, 11h, 12h, 13h, 14h, 15h, etc.
[0038] Optionally, the carbonization step is carried out under a nitrogen atmosphere, and the temperature of the carbonization step is 800-1000℃, for example: 800℃, 850℃, 900℃, 950℃, 1000℃, etc.; the heating rate from room temperature (25-30℃) to the carbonization temperature is 4-6℃ / min, for example: 4℃ / min, 4.5℃ / min, 5℃ / min, 5.5℃ / min, 6℃ / min, etc.
[0039] Optionally, the carbonization time can be 2-4 hours, such as 2 hours, 3 hours, 4 hours, etc., without specific limitations.
[0040] Optionally, the number of water washes after carbonization can be 2-5 times, and the time for each water wash can be 3-7 minutes. The drying temperature after water washing is 80-120℃, such as 80℃, 90℃, 100℃, 110℃, 120℃, etc.; the drying time can be 10-15 hours, such as 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, etc.
[0041] Optionally, the preparation method of carbon aerogel adsorbent material further includes: loading organic amine onto carbon aerogel and then spraying it onto a porous substrate.
[0042] To ensure more reliable spraying of organic amine-loaded carbon aerogel onto porous substrates, the adhesive can be mixed with the organic amine and carbon aerogel before spraying. The specific steps include: mixing the organic amine solution and adhesive, then incorporating the carbon aerogel, stirring thoroughly, spraying the mixture onto the porous substrate, and baking it at 100-110℃ (e.g., 100℃, 102℃, 105℃, 107℃, 110℃) for 1-3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours) until the weight of the porous substrate loaded with the organic amine-modified carbon aerogel no longer changes.
[0043] Optionally, the mass ratio of the adhesive to the organic amine is 15-25:3-7, for example: 15:3, 20:5, 25:7, 17:4, 22:6, etc.; the mass ratio of the organic amine to the carbon aerogel is 3-7:12-18, for example: 5:15, 3:12, 3:13, 4:15, 7:16, 4:17, 5:12, 5:18, etc.
[0044] Alternatively, the porous substrate includes at least one of paper honeycomb, porous ceramics, porous glass, and porous carbon materials.
[0045] Optionally, the adhesive may include polyvinyl alcohol, acrylate, etc., without specific limitations.
[0046] The present invention will be further described in detail below with reference to the embodiments.
[0047] Example 1
[0048] a. Add 100g resorcinol, 1.65g hexadecyltrimethylammonium bromide, 14.6g nickel chloride and 146ml water, stir well, and then add 126mL of formaldehyde aqueous solution with a mass concentration of 37% to obtain a homogeneous mixed solution.
[0049] b. Pour the mixed solution into a mold and seal it. Under heating conditions of 80°C, a carbon aerogel precursor is obtained by sol-gel reaction for 4 days.
[0050] c. The carbon aerogel precursor was dried at 100°C and atmospheric pressure for 12 hours to obtain a dry gel.
[0051] d. The dry gel was carbonized in a high-purity nitrogen atmosphere at a carbonization temperature of 900℃ for 3 hours. The rate of rising from room temperature to the carbonization temperature was 5℃ / min. After washing with water and drying, carbon aerogel was obtained. The number of water washes was 4, with each water wash lasting 5 minutes. The drying temperature was 100℃ and the drying time was 12 hours.
[0052] e. Mix 5g of L-cysteine, 60mL of water and 20g of 815 gel until homogeneous; then add 15g of finely ground 200-mesh carbon aerogel, stir quickly until homogeneous, and let stand for 2 hours to obtain L-cysteine-loaded carbon aerogel.
[0053] L-cysteine-loaded carbon aerogel was sprayed onto corrugated honeycomb paper with dimensions of 255 mm × 125 mm using a high-speed airflow spray gun, increasing the wet weight of the corrugated honeycomb paper by 50 g. Uniformity of the spraying process was ensured, with no clogging. The wet corrugated honeycomb paper was then placed in an oven and heated to 105°C for 2 hours until the weight no longer changed, yielding corrugated honeycomb paper loaded with L-cysteine-modified carbon aerogel.
[0054] Example 2
[0055] a. Add 100g resorcinol, 1.65g hexadecyltrimethylammonium bromide, 14.6g copper nitrate and 146ml water, stir well, and then add 126mL of formaldehyde aqueous solution with a mass concentration of 37% to obtain a homogeneous mixed solution.
[0056] b. Pour the mixed solution into a mold and seal it. Under heating conditions of 90°C, a carbon aerogel precursor is obtained by sol-gel reaction for 4 days.
[0057] c. The carbon aerogel precursor was dried at 120°C and normal pressure for 10 hours to obtain a dry gel.
[0058] d. The dry gel was carbonized in a high-purity nitrogen atmosphere at a carbonization temperature of 800℃ for 4 hours. The rate of temperature rise from room temperature to the carbonization temperature was 4℃ / min. After washing with water and drying, carbon aerogel was obtained. The number of water washes was 4, and the time of each water wash was 5 minutes. The drying temperature was 80℃ and the drying time was 12 hours.
[0059] e. Mix 5g of L-cysteine, 60mL of water and 20g of 815 gel until homogeneous; then add 15g of finely ground 200-mesh carbon aerogel, stir quickly until homogeneous, and let stand for 2 hours to obtain L-cysteine-loaded carbon aerogel.
[0060] L-cysteine-loaded carbon aerogel was sprayed onto corrugated honeycomb paper with dimensions of 255 mm × 125 mm using a high-speed airflow spray gun, increasing the wet weight of the corrugated honeycomb paper by 50 g. Uniformity of the spraying process was ensured, with no clogging. The wet corrugated honeycomb paper was then placed in an oven and heated to 105°C for 2 hours until the weight no longer changed, yielding corrugated honeycomb paper loaded with L-cysteine-modified carbon aerogel.
[0061] Example 3
[0062] a. Add 100g resorcinol, 1g hexadecyltrimethylammonium bromide, 10.83g nickel nitrate and 130ml water, stir well, and then add 110mL of 40% formaldehyde aqueous solution to obtain a homogeneous mixed solution.
[0063] b. Pour the mixed solution into a mold and seal it. Under heating conditions of 50°C, a carbon aerogel precursor is obtained by sol-gel reaction for 6 days.
[0064] c. The carbon aerogel precursor was dried at 80°C and normal pressure for 15 hours to obtain a dry gel.
[0065] d. The dry gel was carbonized in a high-purity nitrogen atmosphere at a carbonization temperature of 1000℃ for 2 hours. The rate of heating from room temperature to the carbonization temperature was 6℃ / min. After washing with water and drying, carbon aerogel was obtained. The number of water washes was 3, and the time for each water wash was 7 minutes. The drying temperature was 80℃ and the drying time was 15 hours.
[0066] e. Mix 7g of imidazolidinone, 80mL of water and 25g of 815 glue until homogeneous; then add 18g of finely ground 200-mesh carbon aerogel, stir quickly until homogeneous, and let stand for 2 hours to obtain imidazolidinone-loaded carbon aerogel.
[0067] Imidazolium-modified carbon aerogel was sprayed onto a corrugated honeycomb paper with dimensions of 255 mm × 125 mm using a high-speed airflow spray gun, increasing the wet weight of the corrugated honeycomb paper to 60 g. Uniformity of the spraying process was ensured, with no clogging. The wet corrugated honeycomb paper was then placed in an oven and heated to 110°C for 1 hour until the weight no longer changed, yielding corrugated honeycomb paper loaded with imidazolium-modified carbon aerogel.
[0068] Example 4
[0069] a. Add 100g of 3-aminophenol, 2g of hexadecyltrimethylammonium bromide, 20g of nickel bromide and 160ml of water, stir well, and then add 140mL of 30% furfural aqueous solution to obtain a homogeneous mixed solution.
[0070] b. Pour the mixed solution into a mold and seal it. Under heating conditions of 70°C, a carbon aerogel precursor is obtained by sol-gel reaction for 5 days.
[0071] c. The carbon aerogel precursor was dried at 120°C and normal pressure for 10 hours to obtain a dry gel.
[0072] d. The dry gel was carbonized in a high-purity nitrogen atmosphere at a carbonization temperature of 800℃ for 3 hours. The rate of temperature rise from room temperature to the carbonization temperature was 4℃ / min. After washing with water and drying, carbon aerogel was obtained. The number of water washes was 5, and the time for each water wash was 3 minutes. The drying temperature was 110℃ and the drying time was 10 hours.
[0073] e. Mix 3g of polyethyleneimine, 80mL of water and 15g of 815 glue until homogeneous; then add 12g of finely ground 200-mesh carbon aerogel, stir quickly until homogeneous, and let stand for 2 hours to obtain polyethyleneimine-loaded carbon aerogel.
[0074] Polyethylene imide-loaded carbon aerogel was sprayed onto corrugated honeycomb paper with dimensions of 255mm × 125mm using a high-speed airflow spray gun, increasing the wet weight of the corrugated honeycomb paper to 40g. Uniform spraying was ensured to prevent clogging. The wet corrugated honeycomb paper was then placed in an oven and heated to 100℃ for 3 hours until its weight no longer changed, yielding corrugated honeycomb paper loaded with polyethylene imide-modified carbon aerogel.
[0075] Example 5
[0076] The difference between Example 5 and Example 1 is that the organic amine in step e is replaced with triethylenetetramine, while the other steps are the same as in Example 1.
[0077] Comparative Example 1
[0078] a. Add 100g resorcinol, 1.65g cetyltrimethylammonium bromide and 146ml water, stir well, and then add 126mL of formaldehyde aqueous solution with a mass concentration of 37% to obtain a homogeneous mixed solution.
[0079] b. Pour the mixed solution into a mold and seal it. Under heating conditions of 80°C, a carbon aerogel precursor is obtained by sol-gel reaction for 4 days.
[0080] c. The carbon aerogel precursor was dried at 100°C and atmospheric pressure for 12 hours to obtain a dry gel.
[0081] d. The dry gel was carbonized in a high-purity nitrogen atmosphere at a carbonization temperature of 900℃ for 3 hours. The rate of rising from room temperature to the carbonization temperature was 5℃ / min. After washing with water and drying, carbon aerogel was obtained. The number of water washes was 4, with each water wash lasting 5 minutes. The drying temperature was 100℃ and the drying time was 12 hours.
[0082] e. Mix 5g of L-cysteine, 60mL of water and 20g of 815 gel until homogeneous; then add 15g of finely ground 200-mesh carbon aerogel, stir quickly until homogeneous, and let stand for 2 hours to obtain L-cysteine-loaded carbon aerogel.
[0083] L-cysteine-loaded carbon aerogel was sprayed onto corrugated honeycomb paper with dimensions of 255 mm × 125 mm using a high-speed airflow spray gun, increasing the wet weight of the corrugated honeycomb paper by 50 g. Uniformity of the spraying process was ensured, with no clogging. The wet corrugated honeycomb paper was then placed in an oven and heated to 105°C for 2 hours until the weight no longer changed, yielding corrugated honeycomb paper loaded with L-cysteine-modified carbon aerogel.
[0084] Comparative Example 2
[0085] The difference between Comparative Example 2 and Example 1 is that steps a to d are not required to prepare carbon aerogel. Step e is performed using only wood charcoal to load L-cysteine onto the wood charcoal and obtain corrugated honeycomb paper with L-cysteine-modified wood charcoal.
[0086] Comparative Example 3
[0087] The difference between Comparative Example 3 and Example 1 is that steps a to d are not required to prepare carbon aerogel. Instead, step e is performed using coconut shell carbon to load L-cysteine onto the coconut shell carbon, and corrugated honeycomb paper with L-cysteine-modified coconut shell carbon is obtained.
[0088] Comparative Example 4
[0089] Comparative Example 4 is untreated charcoal.
[0090] Comparative Example 5
[0091] Comparative Example 5 is untreated coconut shell charcoal.
[0092] Experimental Example 1
[0093] 0.15 g of each of the carbon aerogels from Example 1, Example 2, Comparative Example 1, Comparative Example 4 (wood charcoal), and Comparative Example 5 (coconut shell charcoal) were collected under a liquid nitrogen atmosphere at 77 K as samples. Nitrogen was used as the adsorbent, and the pore structure of each sample was measured. The pretreatment of each sample involved degassing at 200 °C for approximately 12 hours until the residual pressure inside the sample was below 10 kJ / L. -3 Following the nitrogen isothermal adsorption test, the BET (Specific Surface Area and Pore Size Analyzer) parameter, P / P0 (P: partial pressure; P0: saturated vapor pressure), was converted to adsorption amounts ranging from 0.05 to 0.25, and the slope of the straight line was used to calculate the BET specific surface area. Additionally, the total pore volume was calculated based on the adsorption amount at P / P0 = 0.99. The results are shown in Table 1.
[0094] Table 1
[0095]
[0096] As shown in Table 1, the preparation method of the present invention successfully prepared carbon aerogels with abundant mesoporous structures, and the pore size distribution was concentrated in the range of 10-40 nm.
[0097] Experimental Example 2
[0098] The toluene removal capabilities of the carbon aerogel of Example 1, the carbon aerogel of Example 2, the carbon aerogel of Comparative Example 1, the wood charcoal of Comparative Example 4, and the coconut shell charcoal of Comparative Example 5 were tested.
[0099] Inside a 60L sealed chamber, 0.5g of each sample to be tested was weighed and placed on top of a fan. Approximately 3 μL of analytical grade toluene solution was injected, and the toluene concentration was detected using a Gastec toluene detection tube, recorded as the initial concentration n1. Simultaneously with the fan turned on, the residual toluene concentration n2 was measured after 10, 20, and 30 minutes, respectively. Toluene removal rate = [1 - n2 / n1] × 100%. The test results are shown in Table 2.
[0100] Table 2
[0101]
[0102] As can be seen from Table 2, carbon aerogel has a significant advantage in toluene removal performance compared to coconut shell charcoal and wood charcoal.
[0103] Experimental Example 3
[0104] The formaldehyde adsorption performance of the corrugated honeycomb paper with L-cysteine-modified carbon aerogel in Example 1, the corrugated honeycomb paper with L-cysteine-modified carbon aerogel in Example 2, the corrugated honeycomb paper with L-cysteine-modified carbon aerogel in Comparative Example 1, the corrugated honeycomb paper with L-cysteine-modified lignocarbon in Comparative Example 2, and the corrugated honeycomb paper with L-cysteine-modified coconut shell carbon in Comparative Example 3 was tested.
[0105] Each corrugated honeycomb paper sample to be tested was placed inside a honeywell HHT290 tower air purifier, and formaldehyde CADR was tested in a 30 cubic meter chamber according to GB / T 18801-2022. The test results are shown in Table 3.
[0106] Table 3
[0107]
[0108]
[0109] Table 3 shows that the FCADR of the carbon aerogel filter element was 102 (Comparative Example 1), 118 (Example 2), and 121 (Example 1), while the FCADRs of the modified wood charcoal and coconut shell charcoal filters were 78 and 42, respectively. This indicates that the modified carbon aerogel, due to its abundant mesopores, can better provide channels for formaldehyde adsorption and amino group capture sites, which is superior to wood charcoal and coconut shell charcoal treated with the same formulation. The pore size of wood charcoal or coconut shell charcoal is relatively concentrated around 2 nm, and the pores are easily blocked by the organic amine-modified carbon aerogel, meaning that wood charcoal and coconut shell charcoal are difficult to load with organic amine reagents.
[0110] Both Cu-doped carbon aerogel (Example 2) and Ni-doped carbon aerogel (Example 1) achieved better formaldehyde removal performance than undoped carbon aerogel. This is because the metal-organic amine complex contains an effective weak coordination bond, which can promote the orderly arrangement of organic amine molecules, thereby improving the formaldehyde reaction efficiency.
[0111] Experiment Example 4
[0112] The high-temperature stability of the corrugated honeycomb paper with L-cysteine-modified carbon aerogel in Example 1, the corrugated honeycomb paper with L-cysteine-modified carbon aerogel in Example 2, the corrugated honeycomb paper with L-cysteine-modified carbon aerogel in Comparative Example 1, the corrugated honeycomb paper with L-cysteine-modified lignocarbon in Comparative Example 2, and the corrugated honeycomb paper with L-cysteine-modified coconut shell carbon in Comparative Example 3 was tested.
[0113] The samples to be tested were placed in an oven at 60℃ for 3 days to age, and the stability of their formaldehyde removal performance was compared. The results are shown in Table 4.
[0114] Table 4
[0115]
[0116]
[0117] The carbon aerogel without metal ions in Comparative Example 1 showed a degradation rate of 13%, which was better than that of wood charcoal (Comparative Example 2) and coconut shell charcoal (Comparative Example 3) containing metal ions. Although the carbon aerogel doped with copper ions (Example 2) achieved a good initial FCADR, its degradation rate reached 33% with aging. The carbon aerogel doped with nickel ions (Example 1) showed the lowest degradation rate. Therefore, considering high-temperature stability, nickel ions are the best doping choice.
[0118] In summary, the preparation method of the carbon aerogel adsorbent material of the present invention first prepares a mesoporous metal ion-doped carbon aerogel precursor with tunable pore structure, which is composed of interconnected spherical nanoparticles, has a high specific surface area and a well-developed pore structure, and can provide sufficient channels for the transport of formaldehyde gas molecules. Then, an organic amine is loaded onto the metal ion-doped carbon aerogel precursor, which can fully react with formaldehyde to achieve a highly selective removal effect of formaldehyde. Furthermore, the removal of formaldehyde through the chemical reaction between organic amine and formaldehyde can avoid the problem of secondary pollution caused by the release of formaldehyde at high temperatures, thus ensuring the stability of formaldehyde removal at high temperatures.
[0119] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. The application of corrugated honeycomb paper loaded with L-cysteine-modified carbon aerogel in formaldehyde adsorption, characterized in that, The method for preparing the corrugated honeycomb paper loaded with L-cysteine-modified carbon aerogel is as follows: Add 100g resorcinol, 1.65g hexadecyltrimethylammonium bromide, 14.6g nickel chloride and 146mL water, stir well, and then add 126mL of formaldehyde aqueous solution with a mass concentration of 37% to obtain a homogeneous mixed solution. The mixed solution was poured into a mold and sealed. The carbon aerogel precursor was obtained by sol-gel reaction at 80°C for 4 days. The carbon aerogel precursor was dried at 100°C and normal pressure for 12 hours to obtain a dry gel. The dry gel was carbonized in a high-purity nitrogen atmosphere at a carbonization temperature of 900℃ for 3 hours. The rate of heating from room temperature to the carbonization temperature was 5℃ / min. After washing with water and drying, carbon aerogel was obtained. The number of water washes was 4, with each water wash lasting 5 minutes. The drying temperature was 100℃ and the drying time was 12 hours. Mix 5g of L-cysteine, 60mL of water and 20g of 815 glue until homogeneous; then add 15g of finely ground 200-mesh carbon aerogel, stir quickly until homogeneous, and let stand for 2 hours to obtain L-cysteine-loaded carbon aerogel. L-cysteine-loaded carbon aerogel was sprayed onto a corrugated honeycomb paper with dimensions of 255mm × 125mm using a high-speed airflow spray gun, increasing the wet weight of the corrugated honeycomb paper by 50g. Ensure uniform coating process without clogging; place wet corrugated honeycomb paper in an oven, heat to 105℃, and bake for 2 hours until the weight no longer changes, to obtain corrugated honeycomb paper loaded with L-cysteine-modified carbon aerogel.
Citation Information
Patent Citations
High-amino grafted heterogeneous metal doped carbon xerogel as well as preparation method and application thereof
CN104624157A
Preparation method of carbon aerogel
CN104907016A
Carbon-aerogel-based supported organic amine CO2 absorbent and preparation method thereof
CN105478082A
Method for preparing carbon gas gel
CN1583555A